Diagnóstico de movilidad y seguridad peatonal en el sector de la Glorieta Corales de la ciudad de Pereira Risaralda - Murillo Sosa, Michael Stiven; Rodríguez Benavides, Jhon Wilson; Ruiz Lombana, Diana Carolina (Universidad Antonio Nariño, 2022)
This document contains the development of the diagnosis and pedestrian safety in the Glorieta Corales sector. Pereira. For its realization, some objectives were set, the reference framework was investigated, using quantitative - descriptive methodology throughout the work, the results were obtained from the field visits, which show the type of pedestrians circulating on the platforms.